Parâmetros genéticos e caracterização do crescimento inicial de Euterpe edulis - Peres, Marcello Zatta (2022)
Euterpe edulis Mart., popularly called juçara palm, is a species with an important ecological role in fruit production in the Atlantic Forest. The management of its fruits appears as a way to reduce the anthropic pressure caused by the search for its palm